2015
DOI: 10.4081/gh.2015.311
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the environmental contamination of Toxoplasma gondii by georeferencing isolates from chickens in an endemic area in Southeast Rio de Janeiro State, Brazil

Abstract: The environmental contamination of Toxoplasma gondii in an endemic area in Brazil was mapped by georeferencing isolates from chickens in farms in the Southeast of the state of Rio de Janeiro. Tissue samples obtained from 153 adult chickens were analyzed by the mouse bioassay for T. gondii infection. These animals were reared free-range on 51 farms in the municipalities of Rio Bonito and Maricá. The ArcGIS kernel density estimator based on the frequency of T. gondii-positive chickens was used to map the environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In addition to a holistic approach, recent studies have also shown geoprocessing to be an important tool for better interpretation of spatial characteristics and dynamics of infectious diseases [27,28]. In a northern state ranked fourth on the total Brazilian beef export, seropositive clusters for toxoplasmosis in beef cattle have shown a low impact of the disease despite a widespread undercooked barbecue tradition [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to a holistic approach, recent studies have also shown geoprocessing to be an important tool for better interpretation of spatial characteristics and dynamics of infectious diseases [27,28]. In a northern state ranked fourth on the total Brazilian beef export, seropositive clusters for toxoplasmosis in beef cattle have shown a low impact of the disease despite a widespread undercooked barbecue tradition [29].…”
Section: Introductionmentioning
confidence: 99%
“…In other situations, the use of a spatial approach as an epidemiological tool has been strongly suggested to improve associated risk analysis and prevention of T . gondii through identifying landscape characteristics and mapping environmental contamination [28,3032]. …”
Section: Introductionmentioning
confidence: 99%
“…This difference between trends in chicken and human seroprevalence may be explained at least in part by the behaviour of humans with respect to their constant mobility across areas with diverse risk of T. gondii oocyst groundwater contamination, whereas chickens are confined to the same peridomestic areas during their lifespan and also by the differential habits and hygiene behaviour observed in humans. Regarding this last point, Casartelli-Alves et al (2015) published a study on environmental contamination by T. gondii based on georeferencing isolates from chickens in an endemic area of RJ. The researchers applied questionnaires for risk factors that considered the ingestion of unfiltered and untreated water from natural sources, including wells and rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Ground water would be a more favourable environment than soil for the persistence and “preservation” of oocysts and for the organism's evolution and perpetuation. In fact, soil contamination by T. gondii oocysts is not a stationary event because it can varies depending on the presence of feline excretion of oocysts in faeces and on environmental conditions such as temperature and moisture ( Dubey 2004 , Casartelli-Alves et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation